438. THE NEED FOR INFORMATION AND SUPPORT IN DECISION-MAKING IN PATIENTS WITH ESOPHAGEAL CANCER WHO PREFER STANDARD SURGERY OR ACTIVE SURVEILLANCE. (24th September 2022) - Van Der Zijden, Charlène J; Hermus, M; van der Wilk, BJ; Chang, R; Dekker, JWT; Coene, PPLO; Nieuwenhuijzen, GAP; Rosman, C; Heisterkamp, J; Hartgrink, HH; Wijnhoven, BPL; van Lanschot, JJB; et al.
Abstract: Shared decision making (SDM) is the cornerstone of patient-centered care and is associated with improved treatment outcomes. Making a well-informed decision can be challenging. Patients have to weigh possible outcomes and take into account a certain level of uncertainty. This study investigated patients' information and supportive needs during the decision-making process to prefer active surveillance or standard surgery after neoadjuvant chemoradiotherapy (nCRT) for esophageal cancer. Patients who underwent nCRT for carcinoma of the esophagus or esophagogastric junction and refused participation in a randomized trial on active surveillance versus standard surgery were included. Patients were interviewed about their need for information and support and received questionnaires on information- and decision-making preferences and health literacy 3 months after completion of nCRT or before surgery. Interviews were audiotaped and transcribed verbatim. Data were analyzed according to the principles of grounded theory. Forty patients were included of which 20 preferred surgery and 20 preferred active surveillance. Overall, patients' information needs were met. Patients highly value support received from their loved ones and appreciate emphatic doctors who actively involved them in the decision-making process while paying attention to their individual needs and values. Information resources as the internet and conversations with others were largely used to confirm the treatment decision. Patients prefer to receive information from doctors first and they predominantly rely on this information to make a treatment decision. The importance of shared decision making and the role of doctors in this process is underlined by patients' wish to be guided in decision-making. The role of healthcare professionals is essential at the initial phase of the decision-making process. After patients seem to have made a treatment decision, the influence of extern resources (including doctors) is limited.